Automatic voice recognition in open sets - BASZTURA, Czesław; MAJEWSKI, Wojciech; JURKIEWICZ, Jerzy (Archives of Acoustics, 1988)
Every system of automatic voice recognition can be divided into three parts: the voice source, the measuring system (the system of parameter extraction) and the classifier. The object of interest of the present paper is the classifier, in which emphasis is laid upon the procedure capable of recognizing voices in open sets. The methodology of investigations, analysis of the problem and the recognizing algorithm has been presented. Also the experimental results accounting for choice optimization and extraneous voice discrimination as well as the problem of choosing the threshold values for a given recognition strategy has been discussed.